Differentiation Between Granulomatous Lobular Mastitis and Breast Cancer Using Quantitative Parameters on Contrast-Enhanced Ultrasound - Yin, Liang; Agyekum, Enock Adjei; Zhang, Qing; Pan, Lei; Wu, Ting; Xiao, Xiudi; Qian, Xiao-qin (Frontiers in Oncology, 2022)
Objective: To investigate the Contrast-enhanced ultrasound (CEUS) imaging characteristics of idiopathic granulomatous mastitis (IGM) and the value of differentiating IGM from breast cancer. Materials and methods: Thirty women with IGM (mean age 36.7±5 years [SD]) and 58 women with breast cancer (mean age 48±.8 years [SD]) who were scheduled for ultrasound-guided core biopsy were recruited for the study. Prior to biopsy, all patients were evaluated with conventional US and CEUS. The parameters of the quantitative and qualitative analysis of the CEUS were recorded and compared in both groups. Receiver-operating-characteristics curves (ROC) were created. The values of sensitivity, specificity, cut-off, and area under the curve (AUC) were calculated. Results: IMG had statistically higher TTP values than breast cancer (mean, 27.63±7.29 vs. 20.10±6.11) and lower WIS values (mean, 0.16±0.05 vs. 0.28±0.17). When rich vascularity was found in 54.45 % of breast cancer but only 30.00 % of IGM. ROC test yielded an AUC value of 0.791 and 0.807. Optimal cut-off value for TTP was 24.5s and WIS value was 0.185dB/s, yielding 73.33% sensitivity, 84.48% specificity and 86.21% sensitivity, 70% specificity in WIS for the diagnosis of IGM. The lesion scores reduced from 4 to 3 with the addition of CEUS for the patients with IGM. However, the scores did not change for the patients with breast cancer. Conclusion: CEUS contributes to differentiate IGM from breast cancer with higher TTP and WIS values, thus has potential to influence clinical decision making for further biopsies.